Recombination luminescence in LaPO4-Eu and LaPO4-Pr nanoparticles - Vistovskyy, V.; Malyy, T.; Voloshinovskii, A.; Getkin, A.; Shapoval, O.; Zaichenko, A.; Mitina, N. (Видавництво Львівської політехніки, 2012)
The luminescence properties of LaPO4-Eu and LaPO4-Pr nanoparticles with various sizes (8–50 nm) are studied upon the excitation by VUV and X-ray quanta. The dependences of luminescence intensity on nanoparticle size for nanoparticles LaPO4-Pr and LaPO4-Eu possessing, respectively, by the electron and hole recombination luminescence at the excitation by quanta of various energies are discussed.
Keywords: luminescence; nanoparticles; luminescence excitation spectra in UV and VUV ranges